2010
DOI: 10.1073/pnas.1009513107
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofProchlorococcusclades from iron-depleted oceanic regions

Abstract: Prochlorococcus describes a diverse and abundant genus of marine photosynthetic microbes. It is primarily found in oligotrophic waters across the globe and plays a crucial role in energy and nutrient cycling in the ocean ecosystem. The abundance, global distribution, and availability of isolates make Prochlorococcus a model system for understanding marine microbial diversity and biogeochemical cycling. Analysis of 73 metagenomic samples from the Global Ocean Sampling expedition acquired in the Atlantic, Pacifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
190
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 164 publications
(212 citation statements)
references
References 63 publications
16
190
3
1
Order By: Relevance
“…We also found that sequences mapping to clade c1 (HLIII and HLIV) significantly dominated the Equatorial Pacific Ocean samples (indicator analysis, r.g. = 0.53, P = 0.008) and was consistent with a past analysis of these samples from the region (Rusch et al, 2010). Among HLII clades, c9 (including strain MIT9301) was the most frequent subclade and together with c5, c6 and c7 common across all regions except the California Current, South Atlantic Ocean and Equatorial Pacific Ocean (Supplementary Table S2).…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…We also found that sequences mapping to clade c1 (HLIII and HLIV) significantly dominated the Equatorial Pacific Ocean samples (indicator analysis, r.g. = 0.53, P = 0.008) and was consistent with a past analysis of these samples from the region (Rusch et al, 2010). Among HLII clades, c9 (including strain MIT9301) was the most frequent subclade and together with c5, c6 and c7 common across all regions except the California Current, South Atlantic Ocean and Equatorial Pacific Ocean (Supplementary Table S2).…”
Section: Resultssupporting
confidence: 74%
“…A set of iron-requiring proteins were frequently under-represented in the Equatorial Pacific Oceanperhaps as an adaptation to lower iron availability (Rusch et al, 2010). In our analysis, we recovered a small subset of these orthologous genes (5 out of the 17 non-core genes) (Rusch et al, 2010) as significantly differentiating between regions.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations